Relações de poder, tensões, conflitos e resistências: um estudo etnográfico com um grupo de professoras/es de inglês de um curso de formação continuada - Paula, Charlene Steplany Marylin Meneses de (2018)
This ethnographic research, carried out between 2011 and 2017, has investigated how power networks impact teacher education and performance. Therefore, I have answered the following questions: 1) what stress and conflict situations have risen during the data-generation phase, namely, in the period of methodological transition between the collaborative research and the ethnographic research? 2) what kinds of resistance circumstances have come forth throughout the third module of the continual training? How have they been manifested and understood? I was one of the training professors in a continual training course for teachers of English. I was in charge of a training center in a city of Goiás in 2013, and, over the fieldwork phase, 14 apprentice teachers (12 female and 2 male teachers) participated effectively in 32 four-hour classes during the first or the second semester. The teachers came either from the same city where the center is located or from cities nearby and taught English in schools administered by the state government and/or in schools ruled the city government. The course was held in the training school in the regional education department office located in that city. The meetings were face-to-face and took place every Friday from 2 to 6 p.m. I have developed and reflected on this research having systemic thought, the paradigm of complexity, as a basis for it. In order to guide my analyses, I have used mostly Ginzburg’s index paradigm (1989), Goffman’s concepts of façade interaction and preservation rituals (1974; 2012), as well as Foucault’s studies on power and resistance relations (1988; 1993; 2001; 2004; 2004a; 2008; 2009; 2010; 2011). I reckon that the analysis of interaction events has helped me to comprehend stress situations that lay out of the control of who coordinates the training process (in this case, I) and conflicts for which the the training professor is not (the only) responsible, as well as how varied resistance types to an authority or to counter-conducts may be. The (counter)resistances have led to many conflicts, which, on their turn, have proven to be valuable in bringing benefits or independence. 77,7% of the participants have chosen the third module as the most significant one in the course; they have alleged in some of the results that they still must change their minds when it comes to considering race prejudice; that the course has enabled them to share experiences and to acknowledge new realities; that the texts they read have helped them reflect on how they deal with the world in and out of the school; and that the themes could be shared with students in public basic schools.